Chinese Merchants, Silver Galleons, and Ethnic Violence in Spanish Manila, 1603-1686 - Ruiz-Stovel, Guillermo (México y la Cuenca del Pacífico, 2015)
Between 1565 and 1815, silver-laden galleons made their way across the Pacific almost annually, carrying pieces-of-eight from the port of Acapulco and into the southern Chinese province of Fujian via the port of Manila, returning with raw and finished silk for Spanish American markets. With the arrival of the first galleons, Manila’s Chinese community began to grow dramatically. By 1603 there were an estimated 30,000 Chinese and only a few hundred Spanish settlers. Manila may have been a Spanish possession, but for all practical purposes it was a Chinese town, inhabited not only by Chinese merchants but also by a skilled contingent of workers and artisans who kept the colony afloat. The Sangleyes, as the Manila Chinese were referred to in Spanish, were confined to a walled Chinese ghetto, known as the Parián, and banned from living in the fortified Spanish castle-town of Intramuros. In 1603, 1639, and again in 1686, Chinese uprisings rocked Manila. It is estimated that a total of over 40,000 Chinese migrants were massacred as a result of these revolts. Primary sources describe the existing tension between both Spaniards and Chinese: the exorbitant taxation and residential segregation of the Sangleyes; Spanish fears of being outnumbered and overrun in their own colony. This paper attempts to make sense of these events by taking the revolt of 1603 as a point of departure, followed by a brief discussion of the underlying causes of ethnic violence in Spanish Manila. It then explores the background of Manila’s economic and social structures in order to analyze the Sangley uprisings of the seventeenth century within the context of colonial Manila’s role as the multiracial entrepôt of the trans-Pacific galleon economy. It was in 1603 that the governor of Fujian, under imperial decree, dispatched the assistant magistrate of the port of Haicheng ?? to meet with the chieftain of the so-called Spanish “barbarians” (or xiao xiyang ???). He sailed with a retinue of over a hundred men, and once he met with the governor of Manila, proceeded to inquire about a legendary mountain made of gold allegedly adjacent to Manila Bay, rumors of which had reached as far as the emperor.